2015
DOI: 10.3390/molecules20022816
|View full text |Cite
|
Sign up to set email alerts
|

Novel Zinc-Catalytic Systems for Ring-Opening Polymerization of ε-Caprolactone

Abstract: Polycaprolactone (PCL) is a biodegradable synthetic polymer that is currently widely used in many pharmaceutical and medical applications. In this paper we describe the coordination ring-opening polymerization of ε-caprolactone in the presence of two newly synthesized catalytic systems: diethylzinc/gallic acid and diethylzinc/propyl gallate. The chemical structures of the obtained PCLs were characterized by 1H- or 13C-NMR, FTIR spectroscopy and MALDI TOF mass spectrometry. The average molecular weight of the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 24 publications
3
25
0
Order By: Relevance
“…As was shown, the content of cyclic products generally increased with increasing of the temperature and polymerization time. In our previous paper, we reported that when ROP of CL was carried out in the presence of ZnEt 2 /PGAc catalytic system at 40–60 °C within 48 h or at 80 °C within 6 h, macrocyclic products did not formed [40]. As shown in Table 1, Table 2, Table 3 and Table 4, trends of macrocyclization process during ROP of rac -LA in the presence of ZnEt 2 /PGAc were similar.…”
Section: Resultssupporting
confidence: 52%
See 2 more Smart Citations
“…As was shown, the content of cyclic products generally increased with increasing of the temperature and polymerization time. In our previous paper, we reported that when ROP of CL was carried out in the presence of ZnEt 2 /PGAc catalytic system at 40–60 °C within 48 h or at 80 °C within 6 h, macrocyclic products did not formed [40]. As shown in Table 1, Table 2, Table 3 and Table 4, trends of macrocyclization process during ROP of rac -LA in the presence of ZnEt 2 /PGAc were similar.…”
Section: Resultssupporting
confidence: 52%
“…The same trend was observed in our previous experiments concerning ROP of CL in the presence of ZnEt 2 /PGAc or ZnEt 2 /GAc catalytic systems. This likely demonstrates that only -OZn- active species are formed in the first case (ZnEt 2 /PGAc) whereas in the second case (ZnEt 2 /GAc), -COOZn- species are also formed [40].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The NMR spectra of PVL is shown in Figure . Each characteristic peak of the proton is detected and allocated, conform to the structure of PVL described in previous reports . The methylene signal of PVL is observed around 4.17 ppm while the other chemical peaks of PVL were observed around 2.44, and 1.78 ppm respectively confirming the formation of PVL.…”
Section: Resultsmentioning
confidence: 97%
“…In recent years, the natural polymer hyaluronic acid (HA) has also played an important role in the pharmaceutical field due to its anti-inflammatory, regenerative and anti-age properties. By the same token, polycaprolactone (PCL) is a biodegradable synthetic polyester 26 that has been broadly applied in biomedical fields for the preparation of controlled drug delivery systems such as implants and scaffolds 27,28 . It has been recently combined or co-polymerized with effective natural antioxidants such as vanillic, ferulic, p-coumaric and syringic acids 29 .…”
mentioning
confidence: 99%